2021
DOI: 10.1029/2021jc017186
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Lens Fronts Propagating as Buoyant Gravity Currents in the Equatorial Indian Ocean

Abstract: Freshwater lenses (FWLs) deposited by rain exhibit local anomalies in surface salinity and temperature. The resulting patchiness in near‐surface density and sea surface temperature influence upper ocean dynamics and air‐sea fluxes of heat. Understanding lens formation and evolution has been a focus of recent observational and modeling efforts. The work presented here integrates near‐surface ocean and atmosphere time series with remote sensing of sea surface disturbances (X‐band radar) to describe properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(124 reference statements)
1
12
0
Order By: Relevance
“…The distance between our observations (0.74 ± 0.18 m) was close to the spatial scale needed to resolve this patchiness even though higher resolution data would be optimal. Other studies have also observed a similar heterogeneous patchiness of these freshwater pools located on the surface ocean (Moulin et al., 2021; Shcherbina et al., 2019). Shcherbina et al.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The distance between our observations (0.74 ± 0.18 m) was close to the spatial scale needed to resolve this patchiness even though higher resolution data would be optimal. Other studies have also observed a similar heterogeneous patchiness of these freshwater pools located on the surface ocean (Moulin et al., 2021; Shcherbina et al., 2019). Shcherbina et al.…”
Section: Discussionsupporting
confidence: 57%
“…The distance between our observations (0.74 ± 0.18 m) was close to the spatial scale needed to resolve this patchiness even though higher resolution data would be optimal. Other studies have also observed a similar heterogeneous patchiness of these freshwater pools located on the surface ocean (Moulin et al, 2021;Shcherbina et al, 2019). Shcherbina et al (2019) observed the formation of a 4-m-thick rain lens at the surface, which eventually was dissipated into the larger water mass within 4 hr from the start of the precipitation.…”
Section: Effects From Ar-storm Precipitation On Surface Buoyancy Forcingmentioning
confidence: 61%
“…It is important to note that the 1‐dimensional model framework implemented in this study presents a simplified view of ocean dynamics, neglecting the effects of horizontal processes. Lateral advection and propagation of salinity and temperature anomalies associated with RLs distribute SST and SSS anomalies over a greater area and smooths spatial gradients of these variables (Moulin et al., 2021 ). As such, the extrema of SST gradients and the Laplacian of the SST field in Section 4.4 are likely an overestimate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, freshening by rain can lead to the formation of stable fresh and often colder lenses (e.g., Katsaros & Buettner, 1969; Moulin et al., 2021; Reverdin et al., 2012) that can correspond to a decrease down to −9 g/kg and −1.5 K (Reverdin et al., 2020). Rain lenses are frequent in the tropics where the precipitation rate is high and the wind speed is low (e.g., Drushka et al., 2016; Moulin et al., 2021) but they can also occur at higher latitudes (Supply et al., 2020; Ten Doeschate et al., 2019). In addition, vertical gradients in temperature and salinity exist in the viscous boundary microlayer that typically extends within the first millimeter of the ocean and constitutes the Temperature Boundary Layer (TBL) and the Mass Boundary Layer (MBL), which are the diffusive microlayers for temperature and salinity respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…They are particularly frequent in the tropics but can also be strong and frequent in high latitudes during the summer (Bellenger & Duvel, 2009; Kawai & Wada, 2007; Stuart‐Menteth et al., 2003). On the other hand, freshening by rain can lead to the formation of stable fresh and often colder lenses (e.g., Katsaros & Buettner, 1969; Moulin et al., 2021; Reverdin et al., 2012) that can correspond to a decrease down to −9 g/kg and −1.5 K (Reverdin et al., 2020). Rain lenses are frequent in the tropics where the precipitation rate is high and the wind speed is low (e.g., Drushka et al., 2016; Moulin et al., 2021) but they can also occur at higher latitudes (Supply et al., 2020; Ten Doeschate et al., 2019).…”
Section: Introductionmentioning
confidence: 99%